Peningkatan Mutu Produk Jamu Home Industry pada Kelompok Jamu Gendong Desa Karangrejo Kabupaten Magetan di Masa Pandemi Covid-19 - Cicilia Novi Primiani; Pujiati Pujiati; Mohammad Arfi Setiawan (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The purpose of this community service activity is to improve the quality of jamu gendong products at the home industry of jamu gendong in Karangrejo village, Magetan Regency. The method of service is carried out by training, including procedures for pre-survey activities, surveys, socialization, training, and evaluation. The target of the service activity is the women of the jamu gendong group. The evaluation results showed an increase in participant understanding of 56% about the technique of selecting rhizomes for herbal medicine, an increase in participant understanding of 44% about equipment selection techniques for herbal medicine, an increase in participant understanding of 72% about the hygienic process of making herbal medicine, an increase in participant understanding of 66% about the hygienic packaging process of herbal medicine. The results of monitoring and evaluation showed that 100% of participants were satisfied in participating in the activities, 100% of participants took an active role in participating in the training, 100% of participants were enthusiastic in participating in the activities.